Speeches of Chief Ministers At 49th Meeting of the National Development Council - Planning Commission (Planning Commission, 2001)
Hon’ble Prime Minister, Deputy Chairman of the Planning Commission, Union Cabinet Ministers, Colleague Chief Ministers and friends.
Government of India
Government of India